The survey of Factors Related to Consumption of Omega-3 Supplements Based on the Constructs of Health Belief Model in the Elderly Alzheimer Prevention - zahra jalili; reza tavakoli; sahar jalili (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Threatening 5%-10% of people over 65, Alzheimer's disease (AD) is the most common type of dementia. Studies recommended the consumption of substances containing omega-3 as a way to prevent AD. The aim of present study was to determine factors related to consumption of omega-3 supplements based on the health belief model (HBM) constructs in order to prevent AD among the elderly. Methods: In this analytical cross-sectional study, 333 elderly, who referred to the healthcare centers of Tehran city in 2015-2016, were selected by stratified random sampling method. To be over 60 years old, absence of AD and consumption of omega-3 supplements during the past year, were set as the study entry criteria. Data were collected by a questionnaire developed based on HBM constructs after determining its validity and reliability were determined. The collected data were analyzed using SPSS 16. Results: The highest calculated mean belonged to the Preventive behavior construct 48.6 (P< 0.001) followed by Perceived benefits 42.3 (P< 0.001). The lowest mean value was acquired by the construct of perceived barriers. This study showed that there existed some significant correlations of the behavior of omega-3 supplement consumption with the knowledge and constructs of susceptibility, severity and benefits perceived by the elderly studied. Conclusion: Considering the present study results showing significant relationship of omega-3 supplement consumption with knowledge and majority of HBM constructs, it is suggested that some elderly education interventions be designed and implemented to promote the behavior of AD prevention through strengthening the constructs of HBM.